Aptamer based immunotherapy: a potential solid tumor therapeutic - Mathavan, Sarmilah; Tam, Yew Joon; Mustaffa, Khairul Mohd Fadzli; Tye, Gee Jun (Frontiers in Immunology, 2025)
Aptamer-based immunotherapy can be a new hope for treating solid tumors with personalized and specific approaches toward cancer therapies. Aptamers are small synthetic single-stranded nucleic acids that may bring in a paradigm shift in treating solid tumors. These are highly selective drugs applied in cellular immunotherapy, cytokine modulation, and immune checkpoint suppression. This review provides an overview of the recent advances in aptamer-based technologies with specific key clinical trials involving AON-D21 and AM003. Aptamers are potently active in immune regulation and tumor targeting. However, aptamer stability and bioavailability are seriously compromised by the issues relating to renal clearance and rapid degradation through nucleases. The latter are reviewed here along with novel improvements, some of which involve chemical modifications that greatly enhance stability and prolong the circulation time; exemplary such modifications are PEGylation, cholesterol conjugation, and the synthesis of circular nucleic acids. The regulatory aspect is also crucial. For example, in addition to specific strategies to prevent drug-drug interactions (DDIs) in cancer remediation medications, this paper underscores the need of risk assessment, particularly because of immunogenicity and organ failure. The use of aptamers is expanded by the development of SOMAmers, X-aptamers, and bioinformatics. To make aptamer-based drugs a major part of cancer treatment, future research should concentrate more on resolving existing issues and expanding their beneficial uses.